Effects of medial prefrontal cortex cytotoxic lesions in mice. - Deacon, R; Penny, C; Rawlins, J (2003)
Mice (C57BL/6J strain, females) with cytotoxic lesions of the medial wall of the prefrontal cortex were given a battery of tests to assess emotional, species-typical, cognitive, motor and other behaviours. Lesioned mice showed a profile of reduced anxiety, both on a plus-maze, and a similar, novel test, the successive alleys. There was no evidence, however, for attenuation of anxiety in tests of hyponeophagia, and lesioned mice, like controls, preferred the black to the white area of an enclosed alley. Their locomotor activity tended to be higher than that of the controls, particularly when the test surroundings were novel or relatively so. Species-typical behaviours were similar to those of control mice, except lesioned mice displaced ('burrowed') less food pellets from a tube in their home cage. They were not impaired at learning a spatial Y-maze reference memory task, which is profoundly affected by cytotoxic hippocampal lesions in the same strain, or at learning a multi-trial passive avoidance test. Their strength and co-ordination in motor performance tests was also normal. The results show that cytotoxic medial prefrontal cortex lesions in mice produce a clear but restricted anxiolytic action. The marked reduction in burrowing, in the absence of any detectable impairment of motor ability, demonstrates the sensitivity of this behavioural index.